Does accounting conservatism mitigate the shortcomings of CEO overconfidence? - HSU, Charles (Institutional Knowledge at Singapore Management University, 2017)
Overconfident CEOs are more willing to initiate investment projects that require experimentation, yet tend to defer responding to the bad news when the project is not performing as planned. Accounting conservatism accelerates the recognition of the bad news and its dissemination to gatekeepers, making it more likely that the CEO will acknowledge the problem earlier and start searching for solutions. Therefore, firms where both characteristics-CEO overconfidence and accounting conservatism-are present should perform better. Our empirical tests confirm this prediction: firms that practice conservative accounting and are run by overconfident CEOs exhibit better cash flow performance. Our results continue to hold in a variety of settings, including market reactions to acquisitions, cash flow downside risk, and analyst following. Further, the joint positive effect of CEO overconfidence and accounting conservatism on firm performance is stronger in high-uncertainty environments and in firms facing less stringent financing constraints, consistent with theoretical predictions.